The history of the German Criminal Code - Satolin, Vladimir N.; Hellmann, Uwe (Journal of the Belarusian State University. Law, 2019)
This paper depicts the moral foundations of German criminal law, the development of the Criminal Code, embodied in several criminal offences, the wording of which remains almost identical to those in the Prussian Criminal Code from 1851, and the particulars of Juvenile criminal law, set out in the Juvenile Court Act. Finally, this paper offers an overview of the numerous changes made to the Criminal Code since 1949.